Dealing with feeling : use your emotions to create the life you want - Brackett, Marc A. (Celadon Books, 2025)
"From Marc Brackett, director of the Yale Center for Emotional Intelligence and author of the bestselling book Permission to Feel, comes an essential guide for regulating how we respond to our emotions in order to transform our lives Success in virtually every aspect of life-career, friendships, love, family-is determined mainly by one thing: how you deal with your feelings. In your most challenging moments, how did you respond? Did you fly off the handle? Were you paralyzed by indecision? Did you engage in behaviors that undermined your best intentions? Or, did you exhibit grace under pressure and flourish? How you responded likely determined what happened next. But the way we handle our emotions is not, as many believe, a fixed part of ourselves. Rather, it is a set of skills and techniques that must be taught and refined across our lives. Marc Brackett examines his own experiences with emotions, explains the latest science of emotion, and provides a set of practical, evidence-based strategies to help readers use their feelings wisely to nurture healthy relationships, achieve challenging goals, and attain greater wellbeing. At the heart of his message is acceptance; there is no such thing as a bad emotion-only the ones you don't understand and don't yet know how to direct in positive, intentional ways. We all have the power to decide how we will respond to what life throws at us. By honing our emotion regulation skills, we can increase our chances of achieving success in all facets of our lives. Dealing With Feeling will help you become the best version of yourself"-- Provided by publisher.